Dual driven mechanism (hygro‐redox) semi‐interpenetrating polymer network composite film (polyaniline‐polyacrylic acid/sulfonated poly (ether ether ketone)) for artificial muscles. (29th April 2022) - Kareem, Haval; Langrock, Alex; Auletta, Jeffrey; Mahoney, Luther; Hallinan, Daniel; Kim, Hyun; Leff, Asher C.; Tran, Dat T.; Mackie, David
Abstract: Different weight ratios of polyaniline (PANI) to poly (acrylic acid) (PAA) were synthesized as interpenetrating polymer networks and blended with sulfonated poly (ether ether ketone) (SPEEK). In‐situ polymerization was performed by chemical oxidation of aniline in the presence of PAA. The composites showed actuation capability in the presence of fuel/air and moisture. Mechanical testing indicated that samples with higher concentration of PAA were stronger. For instance, PANI1 PAA2 SPEEK3 breaks at 8.4 MPa and has a failure strain of 2.5%, which is higher than PANI3 PAA1 SPEEK3 at 7 MPa and 2%. However, higher amount of PAA resulted in a lower electrochemical conductivity of 1.52 × 10 −2 S/cm for the former and 1.8 × 10 −2 S/cm for the latter. Intermolecular interaction at the optimum composition is necessary to induce forward and reverse bending of catalyst coated composite under exposure of fuel and air. In addition, the formation of compact structures and rough surfaces resulted in the maximal contractile strain of 1% for PANI3 PAA1 SPEEK3 based on moisture actuation.